Locating Early Modern Orientalism: Epistemology, Empire, and European Consciousness (KULT_online, 2019)
Orientalism as conceived by Edward Said has had a lasting influence and it has produced notions that scholars from humanities are still working to nuance and clarify. The Dialectics of Orientalism in Early Modern Europe, edited by Marcus Keller and Javier Irigoyen-García, a contribution to a subfield that is still understudied, challenges the view that Orientalism of the sixteenth and seventeenth centuries was similar to that of the two centuries that followed. Constructing their approach on the Hegelian theory of thesis – antithesis – synthesis, the authors highlight the fundamental differences that were in place in the engagements of the humanists of the period with the Oriental Other. The authors cover vast geographical areas and frontiers as well as topics such as empire building, epistemology of the Orient, and the formation of an imaginary Europe.